Język równościowy w nauczaniu DaF na poziomie uniwersyteckim – postawy osób uczących i studiujących wobec jego zastosowania w praktyce dydaktycznej: - Błaszkowska, Hanka (Neofilolog, 2024)
This paper focuses on gender-fair language and the attitudes of teachers and students of German as a foreign language (DaF) towards its use in university teaching. In the context of the survey study presented here, gender is understood as a construct that is manifested in specific, changing language use variants, such as in personal names. The surveyed teachers and students of applied linguistics at the University are current and future DaF linguists and educators, who, due to social changes, will be increasingly confronted with the issues under study in their professional lives. The aim of the study is, firstly, to determine whether gender-fair language is addressed in the DaF courses under study, if so, in what form and to what extent, and secondly, to record and describe the attitudes of the studied groups towards it, in order to raise awareness of this important phenomenon of contemporary German language use. Consequently, the conducted survey provides information about the presence of gender issues in DaF courses and the attitudes of the two groups towards gender-fair language. The results of the study are discussed in terms of their contribution to the development of gender-sensitive didactics of German as a foreign and as a second language.